A STUDY ON BUYING AND REFERRING THE PRODUCT PATTERN OF RURAL CONSUMERS IN PUDUKKOTTAI CITY - C. Rajalingom; D. Elangovan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The digital technology and improved infrastructure, rural consumers are now exposed to a wide range of products and services. However, their buying behavior remains distinct from urban consumers due to cultural, economic, and social factors. Understanding these patterns can help businesses. Understanding rural consumer behavior is essential for businesses aiming to penetrate and sustain in rural markets. This study explores the purchasing patterns of rural consumers, their decision-making process, brand preferences, and the role of word-of-mouth referrals. The research highlights key factors influencing buying behavior, including socio-economic conditions, cultural influences, product availability, and digital penetration. The findings provide valuable insights for marketers to devise effective strategies for engaging rural consumers.